2017
DOI: 10.1371/journal.pone.0178807
|View full text |Cite
|
Sign up to set email alerts
|

Chest-MRI under pulsatile flow ventilation: A new promising technique

Abstract: ObjectivesMagnetic resonance imaging (MRI) of the chest has long suffered from its sensitivity to respiratory and cardiac motion with an intrinsically low signal to noise ratio and a limited spatial resolution. The purpose of this study was to perform chest MRI under an adapted non invasive pulsatile flow ventilation system (high frequency percussive ventilation, HFPV®) allowing breath hold durations 10 to 15 times longer than other existing systems.MethodsOne volunteer and one patient known for a thymic lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…In particular, the reliability of volume measurements close to the lung bases needs confirmation. Although the respiratory stabilization method used (21) greatly diminishes motion compared to free-breathing acquisitions, residual motion artifacts may remain, particularly at the lung bases. Related to this issue, it also remains to be ascertained that respiratory stabilization can also be reliably achieved in patients with lung disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the reliability of volume measurements close to the lung bases needs confirmation. Although the respiratory stabilization method used (21) greatly diminishes motion compared to free-breathing acquisitions, residual motion artifacts may remain, particularly at the lung bases. Related to this issue, it also remains to be ascertained that respiratory stabilization can also be reliably achieved in patients with lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…We also compared the CT and UTE-MR volumetric assessment of a real nodule incidentally detected in the upper part of the right upper lobe of a volunteer from a recent study that explored a new technique allowing prolonged apnea-like MR acquisition performed at full inspiration (21). UTE acquisition was carried out during a 6-min long respiratory stabilization period.…”
Section: Methodsmentioning
confidence: 99%
“…For each volunteer, the UTE acquisition was carried out during a 6‐minute long respiratory stabilization period. Stabilization was achieved with HF‐NIV using a Monsoon III ventilator (Acutronic Medical Systems, Hirzel, Switzerland) and a noninvasive patient interface (Phasitron; Percussionaire, Sandpoint, ID) at a respiratory rate of 250 per minute as previously published . In summary, subjects were ventilated delivering small tidal volumes, around 50 ml, at high frequency, which allows supporting gas exchange, in particular CO 2 clearing, and thus limits the need to breathe.…”
Section: Methodsmentioning
confidence: 99%
“…A technique allowing high‐resolution MRI of the lung at an end‐inspiratory volume could approach the appearance of CT, facilitating intermodality comparison, and thus make it a viable alternative in clinical practice. High‐frequency noninvasive ventilation (HF‐NIV) has been recently applied to achieve respiratory stabilization at inspiratory volume during multiple minutes for radiotherapy and an initial pilot study subsequently demonstrated the feasibility of this technique for MRI . However, a systematic evaluation of the image quality obtained with this new technique remains to be carried out.…”
mentioning
confidence: 99%
See 1 more Smart Citation